Identification of storage conditions stabilizing extracellular vesicles preparations. Issue 6 (18th June 2022) - Görgens, André; Corso, Giulia; Hagey, Daniel W.; Jawad Wiklander, Rim; Gustafsson, Manuela O.; Felldin, Ulrika; Lee, Yi; Bostancioglu, R. Beklem; Sork, Helena; Liang, Xiuming; Zheng, Wenyi; Mohammad, Dara K.; et al.
Abstract: Extracellular vesicles (EVs) play a key role in many physiological and pathophysiological processes and hold great potential for therapeutic and diagnostic use. Despite significant advances within the last decade, the key issue of EV storage stability remains unresolved and under investigated. Here, we aimed to identify storage conditions stabilizing EVs and comprehensively compared the impact of various storage buffer formulations at different temperatures on EVs derived from different cellular sources for up to 2 years. EV features including concentration, diameter, surface protein profile and nucleic acid contents were assessed by complementary methods, and engineered EVs containing fluorophores or functionalized surface proteins were utilized to compare cellular uptake and ligand binding. We show that storing EVs in PBS over time leads to drastically reduced recovery particularly for pure EV samples at all temperatures tested, starting already within days. We further report that using PBS as diluent was found to result in severely reduced EV recovery rates already within minutes. Several of the tested new buffer conditions largely prevented the observed effects, the lead candidate being PBS supplemented with human albumin and trehalose (PBS‐HAT). We report that PBS‐HAT buffer facilitates clearly improved short‐term and long‐term EV preservation for samples stored at ‐80°C, stability throughout several freeze‐thaw cycles, and drastically improved EV recovery when using a diluent for EV samples for downstream applications.